Training-induced plasticity of the social brain in autism spectrum disorder - Bölte, Sven (The British journal of psychiatry, 2018)
Background: Autism spectrum disorder (ASD) is linked to social brain activity and facial affect recognition (FAR). Aims: To examine social brain plasticity in ASD. Method: Using FAR tests and functional magnetic resonance imaging tasks for FAR, we compared 32 individuals with ASD and 25 controls. Subsequently, the participants with ASD were assigned to FAR computer-aided cognitive training or a control group. Results: The ASD group performed more poorly than controls on explicit behavioural FAR tests. In the scanner, during implicit FAR, the amygdala, fusiform gyrus and other regions of the social brain were less activated bilaterally. The training group improved on behavioural FAR tests, and cerebral response to implicit affect processing tasks increased bilaterally post-training in the social brain. Conclusions: Individuals with ASD show FAR impairments associated with hypoactivation of the social brain. Computer-based training improves explicit FAR and neuronal responses during implicit FAR, indicating neuroplasticity in the social brain in ASD.
Gesehen am 03.12.2018
Published online: 02 January 2018